Role of collaboration in innovation success: differences for large and small businesses - González-Benito, Óscar; Muñoz-Gallego, Pablo A.; García-Zamora, Evelyn (Journal of Business Economics and Management, 2016)
This article analyses the role of collaboration in the contribution of innovation to business performance. Moreover, the analysis considers business size as a key control variable to understand the moderating role of collaboration in innovation success. A survey administered to Spanish firms from industrial, building, agriculture, and trade-service sectors measured two levels of innovation, incremental and radical, and two dimensions of collaboration, channel and consulting advice. The findings show that the probability of success increases when firms use collaboration to support innovation efforts. In addition, small businesses take more advantage of channel collaboration, whereas large businesses rely more on consulting advice-based collaboration. These findings suggest that the convenience of different collaboration approaches depend on business size. Also small and large firms differ on the way they might get additional advantages from alternative ways of collaboration. Therefore, the main contribution is the understanding of how innovation success depends on the interaction between the collaboration approach and business size.